Avaliação da densidade do transportador dopaminérgico utilizando [99mTc]-TRODAT-1 e SPECT após privação de sono - Silva, Raquel Cristina Martins da [UNIFESP] (2009)
One inherent repercussion to societal development is the sleep deprivation (SD) during the week followed by sleep compensation on weekends. Because REM sleep predominates in the latter half of the night, people who sleep less may lose REM sleep. Here, we report whether two nights of total SD or four nights of selective REM SD followed by three nights of sleep recovery changes polysomnographic pattern of sleep and dopamine transporter (DAT) density compared to a control group. Single positron emission computed tomography and [99mTc]TRODAT-1 were used to assess cerebral DAT density in the striatum at baseline, after total and REM SD and sleep recovery in healthy volunteers (n=10/group). Blood was collected daily in order to examine prolactin and estradiol levels and correlate these markers with dopaminergic activity. The total SD group exhibited a marked increased in slow wave sleep during the first night of recovery and regular sleep architecture was restored after the first night. However, the REM SD group had longer lasting effects on percentage of REM sleep seen during all the recovery period. Neither total and REM SD affected DAT density in striatum or the levels of cortisol, estradiol and prolactin during the protocol. Because DA activity has been related to REM sleep and selective loss of REM sleep creates a greater imbalance in sleep architecture than total SD, these findings are consistent with recent studies that indicate a novel role for DA in regulating REM sleep.